+0  
 
0
71
1
avatar

(0.4x+16+(0.3(x-(0.4+16)+20)+0.75(x-(0.4x+16))-(0.3(x-0.4x+16)+20)+30=x

 Nov 1, 2019
 #1
avatar+437 
+6

Step 1: Simplify both sides of the equation.

0.4x+16+0.3(x−(0.4+16)+20)+0.75(x−(0.4x+16))−(0.3(x−0.4x+16)+20)+30=x

0.4x+16+(0.3)(x)+(0.3)(−0.4)+(0.3)(−16)+(0.3)(20)+(0.75)(x)+(0.75)(−0.4x)+(0.75)(−16)+(−0.3)(x)+(−0.3)(−0.4x)+(−0.3)(16)+−20+30=x(Distribute)

0.4x+16+0.3x+−0.12+−4.8+6+0.75x+−0.3x+−12+−0.3x+0.12x+−4.8+−20+30=x

(0.4x+0.3x+0.75x+−0.3x+−0.3x+0.12x)+(16+−0.12+−4.8+6+−12+−4.8+−20+30)=x(Combine Like Terms)

0.97x+10.28=x

0.97x+10.28=x

Step 2: Subtract x from both sides.

0.97x+10.28−x=x−x

−0.03x+10.28=0

Step 3: Subtract 10.28 from both sides.

−0.03x+10.28−10.28=0−10.28

−0.03x=−10.28

Step 4: Divide both sides by -0.03.

−0.03x

−0.03

=

−10.28

−0.03

x=342.666667

 Nov 1, 2019

36 Online Users

avatar